(untitled) (Global Journal of Human-Social Science, 2020)
Perfecting the review of the annual report of land reclamation is extremely important to reform the annual report system of land reclamation, which is helpful to the effectiveness of land reclamation supervision. The review of the annual report of land reclamation means that the subjects of land reclamation supervision review the materials or data submitted by the supervised units to realize the supervision of land reclamation activities. This article uses the research method of normative analysis to examine the relevant norms of the review of land reclamation annual report by analyzing the completeness and rationality of the review subjects and review methods of land reclamation annual report, and tries to propose to coordinate the supervision of supervisory departments and improve the working quality of supervisors in order to improve the supervisory capability of the subjects of the annual report of land reclamation, and tries to refine the off-site supervision and strengthen the coordination of off-site supervision and on-site inspection to improve the review methods of the annual report of land reclamation systematically, which will provide specific guidance for the existing review clauses.